The interrupted tale - Wood, Maryrose (Wood, Maryrose. Incorrigible children of Ashton Place, 2013)
When Miss Penelope Lumley receives an invitation to speak at her alma mater on the occasion of the Celebrate Alumnae Knowledge Exposition, she expects the trip to be a piece of cake -- or rather, CAKE. But preparing a great oration in the style of Cicero is the least of her problems. The Swanburne board of trustees is now led by none other than Judge Quinzy, and Baroness Hoover is wreaking mayhem on the school's beloved traditions. Meanwhile, Lord Fredrick has demanded some rather unexpected lessons of his own -- and why on earth have the Swanburne girls stopped using the hair poultice? Something strange is afoot at the Swanburne Academy for Poor Bright Females. But with the help of a friendly pirate, some talented chickens, those clever Incorrigible children, and her own substantial reserves of pluck, Penelope won't be easily defeated. She's determined to give her speech, save the school, unmask Judge Quinzy and find out precisely what lies within the blurry pages of that strange diary about shipwrecks and cannibals she found in Lord Fredrick's library. Too bad the pages are unreadable, or are they? - Author website.